Immediate periodontal bone plate changes induced by rapid maxillary expansion in the early mixed dentition: CT findings - Daniela Gamba Garib; Maria Helena Ocké Menezes; Omar Gabriel da Silva Filho; Patricia Bittencourt Dutra dos Santos (Dental Press Editora, 2014)
OBJECTIVE: This study aimed at evaluating buccal and lingual bone plate changes caused by rapid maxillary expansion (RME) in the mixed dentition by means of computed tomography (CT). METHODS: The sample comprised spiral CT exams taken from 22 mixed dentition patients from 6 to 9 years of age (mean age of 8.1 years) presenting constricted maxillary arch treated with Haas-type expanders. Patients were submitted to spiral CT scan before expansion and after the screw activation period with a 30-day interval between T1 and T2. Multiplanar reconstruction was used to measure buccal and lingual bone plate thickness and buccal bone crest level of maxillary posterior deciduous and permanent teeth. Changes induced by expansion were evaluated using paired t test (p < 0.05). RESULTS: Thickness of buccal and lingual bone plates of posterior teeth remained unchanged during the expansion period, except for deciduous second molars which showed a slight reduction in bone thickness at the distal region of its buccal aspect. Buccal bone dehiscences were not observed in the supporting teeth after expansion. CONCLUSION: RME performed in mixed dentition did not produce immediate undesirable effects on periodontal bone tissues.